Proximal Point Algorithm for Nonexpansive Mappings in Hadamard Spaces Based on SRJ Iteration Process - Dashputre, Samir; Tiwari, Rakesh; Shrivas, Jaynendra (International Journal of Applied Mathematical Research, 2023)
In this paper, We provide a new modified proximal point approach utilizing fixed point iterates of nonexpansive mappings in Hadamard space and show that the sequence created by our iterative process converges to a minimizer of a convex function and a fixed point of mappings. Finally, we present a numerical illustration for supporting our main result. Our results obtained in this paper improve, extend and unify results of Khan-Abbas [23], Cholamjiak et al. [10] and Dashputre et al. [11].